Ambiguitas Terjemahan Kata Uff dalam Standar Penerjemahan Alquran di Indonesia - Muhamad Arju Shidqol Yaqin (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2026)
This study examines the semantic reduction of the Qur'ānic expression uff in standard Indonesian translations, arguing that its rendering as the interjection ah fails to preserve its sound-symbolic and pragmatic dimensions. It aims to reconstruct a more comprehensive translation of uff within the Indonesian linguistic context. This qualitative library research employs Paul Ricoeur's hermeneutic framework—understanding, explanation, and appropriation—integrated with Leanne Hinton's theory of sound symbolism. The analysis is based on Al-Qur'an dan Terjemahnya (Kemenag RI, 2019), supported by classical and contemporary tafsīr literature. The findings reveal inconsistent translation strategies across three Qur'ānic passages. In the context of filial ethics, uff is translated literally as ah in QS. al-Isrāʾ [17]: 23 and QS. al-Aḥqāf [46]: 17, whereas in Abraham's dialogue with his people (QS. al-Anbiyāʾ [21]: 67) it is rendered interpretively as celakalah. These shifts reduce uff from a minimum ethical expression into context-dependent lexical meanings, obscuring its broader communicative function. This study proposes adopting Abdel Haleem's generalization model, which translates uff as